The management audit in Peru and its impact on business development - Valeriano Ortiz, Luis Fernando (2020)
This article is developed based on the importance and significance of assessing the mechanisms of prior, concurrent or simultaneous and subsequent control in the private and public management of the country in order to neutralize the sources of corruption and to optimize private business management and public. The National Control System, whose governing body is the Comptroller General of the Republic, whose scope of application is in the national public sector, in recent decades it has not fulfilled its functions in an efficient and effective manner established by the Political Constitution of Peru, and its regulatory norms, in addition the General Congress of the Republic is regulated by its internal regulations, which have the force of law, not allowing the Comptroller General of the Republic to fulfill its oversight function, the shortage of budgetary resources, Due to these and other considerations, it assumes a precarious and inconsequential role in the preservation of national resources, affecting the national treasury. In private activity, the panorama is similar, it is limited to complying with those established in the legal framework, presenting its financial statements audited annually by national and international private companies or auditing companies. The financial, economic, administrative and management control filters are weak and in some cases do not reflect the reality of business or institutional management. The vast majority of auditors require training, specialization and improvement in matters of public and private control, in addition they must prove moral solvency, ethics and professional deontology, the auditees must know the technical control standards to comply with them rigorously, and the final results of The audits must be objective, in accordance with technical processes and legality.